STRATEGIES FOR RETAILING AND SUPPLY OF FURNITURE - Genchev, Yancho (Innovation in Woodworking Industry and Engineering design, 2012)
The choice of supply strategy and retailing of products is an important element of the corporate design and management. Many different in nature factors have impact on this choice, such as the level of furniture manufacturing, the type of corporate organization and design, the designation of production and approach towards socio cultural environment, etc.